2015
DOI: 10.1093/mnras/stv1405
|View full text |Cite
|
Sign up to set email alerts
|

QUIJOTE scientific results – I. Measurements of the intensity and polarisation of the anomalous microwave emission in the Perseus molecular complex

Abstract: Anomalous microwave emission (AME) has been observed in numerous sky regions, using different experiments in the frequency range ∼ 10 − 60 GHz. One of the most scrutinized regions is G159.6-18.5, located within the Perseus molecular complex. In this paper we present further observations of this region (194 hours in total over ≈ 250 deg 2 ), both in intensity and in polarization. They span four independent frequency channels between 10 and 20 GHz, and were gathered with QUIJOTE, a new CMB experiment with the go… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 56 publications
4
68
0
Order By: Relevance
“…7, together with several regions that have been, or will be, observed by current and future ground-based or ballon-borne CMB experiments. In particular we consider the cases of the LSPE (LSPE Collaboration 2012) and EBEX10K (Chapman et al 2014) proposed balloons, the CLASS (Essinger-Hileman et al 2014), advACT (Calabrese et al 2014), QUIJOTE (Génova-Santos et al 2015), Simons Array ground-based experiment (Suzuki et al 2016), as well as the areas observed by BICEP2/Keck Array (BICEP2 Collaboration I 2014; BICEP2 and Keck Array Collaborations 2015), SPT (Benson et al 2014) and PolarBear (The Polarbear Collaboration 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7, together with several regions that have been, or will be, observed by current and future ground-based or ballon-borne CMB experiments. In particular we consider the cases of the LSPE (LSPE Collaboration 2012) and EBEX10K (Chapman et al 2014) proposed balloons, the CLASS (Essinger-Hileman et al 2014), advACT (Calabrese et al 2014), QUIJOTE (Génova-Santos et al 2015), Simons Array ground-based experiment (Suzuki et al 2016), as well as the areas observed by BICEP2/Keck Array (BICEP2 Collaboration I 2014; BICEP2 and Keck Array Collaborations 2015), SPT (Benson et al 2014) and PolarBear (The Polarbear Collaboration 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On arcminute scales, the dominant contribution is given by gravitational lensing (GL) owing to deflection of CMB photons by cosmological structures along their travel to the observer. Experiments looking at CMB B modes include the European Space Agency (ESA) Planck satellite (Planck Collaboration I 2015), ground-based experiments like PolarBear (The Polarbear Collaboration 2014), the Simons Array (Suzuki et al 2016), BICEP2 (BICEP2 Collaboration I 2014), the Keck Array (BICEP2 and Keck Array Collaborations 2015), SPT (Benson et al 2014), Advanced ACTPol (Calabrese et al 2014), QUBIC (QUBIC Collaboration 2011), QUIJOTE (Génova-Santos et al 2015), CLASS (Essinger-Hileman et al 2014), and balloonborne instruments, such as EBEX (Chapman et al 2014), SPIDER (Fraisse et al 2013), and LSPE (LSPE Collaboration 2012))…”
Section: Introductionmentioning
confidence: 99%
“…The best constraint comes from the Perseus region, which has significant AME emission and relatively little contaminating synchrotron emission. Battistelli et al (2006) reported a weak detection in Perseus at 3.4 +1.5 −1.9 % at 11 GHz, while later measurements obtained by López-Caraballo et al (2011) using WMAP data found a 2σ limit of <1%; Dickinson et al (2011) have also measured a 2σ limit of <1.4% for Perseus (as well as an upper limit of <1.7% in ρ Ophiuchus), and Génova- Santos et al (2015) found a 2σ limit of <2.8% in Perseus at 19 GHz. Recently, Battistelli et al (2015) have claimed to detect polarized AME emission at 21.5 GHz from RCW 175, an H ii region, where they measured a polarization percentage of (2.2 ± 0.2 (random) ± 0.3 (systematic))% at 21.5 GHz.…”
Section: Limits On Ame Polarizationmentioning
confidence: 90%
“…Fig. 15.-Measured polarization of AME from the Perseus molecular complex (Battistelli et al 2006;Dickinson et al 2011); the dark clouds Lynds 1622 (Mason et al 2009) and ρ Oph (Dickinson et al 2011); the HII regions G159.6-18.5 (López-Caraballo et al 2011;Génova-Santos et al 2015) and RCW176 (Battistelli et al 2015); and the W43r molecular complex (Génova-Santos et al 2016). …”
Section: Discussionmentioning
confidence: 99%